The Role of Ki-67 Immunoexpression in Diagnosis of Molar Pregnancy and Differentiating its Subtypes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objectives: The study is intended to evaluate the role of Ki-67 immunoexpression in the diagnosis of molar pregnancy & differential diagnosis of its subgroups from miscarriage.Methods: Sixty eight formalin-fixed, paraffin- embedded specimens of products of conception , including 1st trimester miscarriage (n=15), partial hydatidiform mole PHM (n=24), complete hydatidiform CHM (n=24) and full term placenta (n=5), all were examined at Histopathology Department of Maternity Teaching Hospital in Erbil, Iraq during the period Sep.2012-Sep.2013. Ki-67 immunohistochemical staining was performed by using the monoclonal antibody MIB-1 and the standard streptavidin-biotin immunoperoxidase method. The labeling index (number of positive nuclei/total number of nuclei) for villous, cytotrophoblasts , syncytiotrophoblasts and stromal cells were evaluated separately. Statistical analysis was carried out by Fisher’s exact test & statistical significance was determined at p < 0.05.Results: The study shows that all villous trophoblastic lesions showed high Ki-67 in all villous components especially cytotrophoblasts, being the highest in CHM mole(>50%) followed by PHM (>20%). Also found a statistically significant differences in immunoexpressins of Ki-67 that was useful in separating miscarriage from CHM, p